1976
DOI: 10.1210/jcem-43-2-436
|View full text |Cite
|
Sign up to set email alerts
|

Free and Protein-Bound Plasma Estradiol-17β During the Menstrual Cycle

Abstract: Methods are described for the measurement of the estradiol-binding capacity of TeBG and of the free, TeBG-bound, and non-specifically protein-bound fractions of plasma estradiol. Each determination used undiluted plasma at 37 C, and a total volume of less than 2.0 ml of plasma was required to complete all the assays. The measurement of the per cent of free estradiol was affected by changes in plasma dilution. The measurement of the other fractions of estradiol was not influenced by changes in either the diluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

1979
1979
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 0 publications
2
21
0
2
Order By: Relevance
“…The proportion of free and bound cortisol was measured in un diluted serum and CSF by equilibrium dialysis [35]. Samples of se rum and CSF taken from each animal in experiment 2 were pooled according to treatment and lime of sample.…”
Section: Measurement O F Free and Bound Cortisolmentioning
confidence: 99%
“…The proportion of free and bound cortisol was measured in un diluted serum and CSF by equilibrium dialysis [35]. Samples of se rum and CSF taken from each animal in experiment 2 were pooled according to treatment and lime of sample.…”
Section: Measurement O F Free and Bound Cortisolmentioning
confidence: 99%
“…In the present study, we found that E 2 could dose-dependently promote the migration of MCF-7 breast cancer cells via up-regulation of MRTF-A and its target genes, MYL9 and CYR61. In addition, these effects were dramatically increased when the concentration of E 2 was higher than 10 29 M. It was reported that the plasma concentration of serum estradiol typically fluctuates in a wide range of 1.7-7.5 Â 10 210 M in the normal menstrual cycle of adult female, and it always decreases to about 1.5-2.5 Â 10 211 M in postmenopausal women [16,17]. Therefore, our results suggested that the MRTF-A signal pathway could be markedly activated when the breast cancer cells were exposed to estrogen at higher physiological levels, and this event might contribute to the excessive estrogen-stimulated breast cancer metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…However, shorter halflife of testosterone than estrogen in women, and more affinity of SHBG to testosterone than to estrogen [10] might lead to the conclusion that low SHBG levels are more likely to cause hyperandrogenism in women.…”
Section: Discussionmentioning
confidence: 99%